Gambling participation among adult Basketball players in Iceland - Margrét Viðarsdóttir 1986- (2018)
Studies in the field of gambling behaviour among Icelandic general public and even Icelandic soccer players are relatively common. Despite that, none studies have been conducted about gambling behaviour among Icelandic basketball players. The purpose of this study was to: i) Examine the prevalence of total participation in gambling activities and problem gambling among Icelandic basketball players, ii) To examine the relationship between problem gambling anxiety, depression and ADHD symptoms in the same population and finally to examine in Icelandic basketball players have been involved in behaviour that could possibly be related to match fixing. Participants in this study were 277, basketball players between 18-42 years old, 61% male and 39% female. Five questionnaires were administered; Gambling behaviour, Problem Gambling Severity Index (PGSI), General Anxiety Disorder – 7 (GAD-7), Patient, Health Questionnaire – 9 (PHQ-9) and ADHD rating scale. These questionnaires were sent to the participants via Facebook. Results show that male basketball players, gamble significantly more than female players. The most common gambling activity by Icelandic basketball players was Lottery, but basketball gambling on foreign website was the second most common activity. Results also showed that 5,4% were problematic gamblers. For male, there was a correlation between problematic gambling and depression, anxiety and ADHD symptoms but not for female. About 28,6% of all participants knew about other players or coaches that had gamble on matches in their own division and 10,9% knew about players that had gambled on results on their own match. Of all participants 12,5% agreed that they had gambled on their own division and 13,3% had gambled on a game that they had played. The results indicate that both match fixing and problematic gambling might possibly be a problem in Icelandic Basketball, and it is important to educate basketball players about possible harmfulness of a regular gambling activity. Keywords: gambling in sports, ...